Metabolomics and transcriptomics analyses reveal the complex molecular mechanisms by which the hypothalamus regulates sexual development in female goats - Qing Li; Tianle Chao; Yanyan Wang; Peipei He; Lu Zhang; Jianmin Wang (BMC Genomics)
Abstract Background The hypothalamus is a critical organ that regulates sexual development in animals. However, current research on the hypothalamic regulation of sexual maturation in female goats remains limited. In this study, we conducted metabolomic and transcriptomic analyses on the hypothalamic tissues of female Jining grey goats at different stages of sexual development (1 day old (neonatal, D1, n = 5), 2 months old (prepuberty, M2, n = 5), 4 months old (sexual maturity, M4, n = 5), and 6 months old (breeding period, M6, n = 5)). Results A total of 418 differential metabolites (DAMs) were identified in this study, among which the abundance of metabolites such as anserine, L-histidine, carnosine, taurine, and 4-aminobutyric gradually increased with the progression of sexual development. These metabolites may regulate neuronal development and hormone secretion processes by influencing the metabolism of histidine and phenylalanine. Through combined transcriptomic and metabolomic analyses, we identified that differentially expressed genes such as mitogen-activated protein kinase kinase kinase 9 (MAP3K9), prune homolog 2 with BCH domain (PRUNE2), and potassium voltage-gated channel interacting protein 4(KCNIP4) may jointly regulate the development and energy metabolism of hypothalamic Gonadotropin-releasing hormone neurons in conjunction with DAMs, including LPC22:5, 2-Arachidonyl Glycerol ether, LPE22:5, and Lysops22:5. Additionally, we elucidated the molecular mechanism through which glutathione metabolism regulates sexual maturation in goats. Conclusions In summary, this study illustrates the dynamic changes in metabolites and mRNA within hypothalamic tissue during postnatal sexual maturation in female Jining grey goats. This research may provide significant scientific insights for future animal breeding.